Fire exclusion and climate change interact to affect long‐term changes in the functional composition of plant communities. Issue 5 (May 2017) - Li, Daijiang; Waller, Donald M.
Abstract: Aim: Plant functional traits allow us to mechanistically link changes in species composition to changes in ecosystem functions. Understanding how and why changes occur in functional composition of plant communities can thus help us better conserve and restore biodiversity. We aim to examine long‐term effects of fire exclusion and climate change on the functional composition of fire‐maintained pine barrens in central Wisconsin. Location: Central Wisconsin, USA. Methods: Using a database that included vegetation data of surveys (1958) and resurveys (2012) of 30 sites, we quantified functional composition (α and β functional diversity, community‐weighted means) of each site at both time periods. We then applied linear regression and linear mixed models to study effects of fire exclusion and climate change on changes in functional composition. Results: We observed shifts towards larger specific leaf area, greater seed mass and other traits related to shade tolerance. These communities thus appear to be undergoing ecological succession, favouring plant adaptions to better harvest light and carbon in darker, warmer and wetter habitats. Functional alpha diversity increased, while functional beta diversity decreased even after controlling for changes in taxonomic diversity. Fire exclusion and climate change both contributed to these increases in local functional diversity but neither is related to the functional homogenization observed. Fire exclusion and climate change also interacted negatively to affect local functional diversity, suggesting that future climate change and succession may soon reduce alpha functional diversity. Main conclusions: Our study provides a rare record of long‐term functional dynamics and demonstrates that fire exclusion and climate change can interact to affect the functional composition of plant communities. Thus, we should consider changes in local ecological conditions as we seek to predict how climate change will affect the functional composition of plant communities.